2018
DOI: 10.3390/molecules23020361
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of Azole Complexes Combined with Silver Nanoparticles

Abstract: Growing antimicrobial resistance is considered a potential threat for human health security by health organizations, such as the WHO, CDC and FDA, pointing to MRSA as an example. New antibacterial drugs and complex derivatives are needed to combat the development of bacterial resistance. Six new copper and cobalt complexes of azole derivatives were synthesized and isolated as air-stable solids and characterized by melting point analyses, elemental analyses, thermogravimetric analyses (TGA), and infrared and ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 42 publications
1
22
0
1
Order By: Relevance
“…The electrochemical properties of the carbon paste surface decorated with Cu C were investigated via EIS and CV using 10.0 mmol L À 1 K 4 Fe(CN) 6 in 10.0 mmol L À 1 KCl as the test electrolyte. Moreover, the presence of metals ions, such as copper ions, was assessed via EDS.We previously studied the synthesis and characterization of copper(II) complexes derived from azole and they have received considerable attention due to their low cost, easy preparation, air-stable and electroactive properties [24][25][26][27] In the CV measurement for the ferri/ferrocyanide couple with CPE and Cu C /CPE ( Figure 1A), the anodic and cathodic peak potentials were observed at almost the same potential values of 0.66 V and À 0.20 V, respectively, with a ΔE of 0.81 V, indicating a quasi-reversible redox reaction. However, the anodic and cathodic peak currents increased by almost 30.6 % and 55.1 %, respectively, with the CPE decorated with Cu C .…”
Section: Electrochemical Properties Of the Carbon Paste Surface Decormentioning
confidence: 99%
“…The electrochemical properties of the carbon paste surface decorated with Cu C were investigated via EIS and CV using 10.0 mmol L À 1 K 4 Fe(CN) 6 in 10.0 mmol L À 1 KCl as the test electrolyte. Moreover, the presence of metals ions, such as copper ions, was assessed via EDS.We previously studied the synthesis and characterization of copper(II) complexes derived from azole and they have received considerable attention due to their low cost, easy preparation, air-stable and electroactive properties [24][25][26][27] In the CV measurement for the ferri/ferrocyanide couple with CPE and Cu C /CPE ( Figure 1A), the anodic and cathodic peak potentials were observed at almost the same potential values of 0.66 V and À 0.20 V, respectively, with a ΔE of 0.81 V, indicating a quasi-reversible redox reaction. However, the anodic and cathodic peak currents increased by almost 30.6 % and 55.1 %, respectively, with the CPE decorated with Cu C .…”
Section: Electrochemical Properties Of the Carbon Paste Surface Decormentioning
confidence: 99%
“…The combination of metals and azoles is a promising strategy to develop new efficient drugs, even against drug-resistant pathogens [ 17 , 18 , 19 , 20 , 21 , 22 ]. The development of these new drugs is related to the complexation of azole derivatives with transition metals that have low toxicity and are biocompatible [ 18 , 23 , 24 ]. Previous studies demonstrated that the resulting complexes may have higher antimicrobial activity than the corresponding free azole ligands, and, in some cases, exceeding that of standard test substances (nystatin) [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, the synthesis and crystalline structure of a monomeric compound of L and CuCl 2 , produced by the reaction of N ‐hydroxymethyl‐3,5‐dimethylpyrazole with CuCl 2 in a 2:1 ratio in ethanol, was reported, supporting the work of Mesubi and Anumba. The reaction between L and CuCl 2 , yielding a yellow complex, has also been previously reported, and the compound is considered to be a monomeric compound, as well , , , . However, the yellow complex had not been characterized by single‐crystal X‐ray diffraction, which led us to inquire about the structural identity of this compound.…”
Section: Introductionmentioning
confidence: 89%